Registration of 'LCS Compass' Wheat. Issue 1 (13th December 2018) - Liu, L.; Barnett, M. D.; Griffey, C. A.; Malla, S.; Brooks, W. S.; Seago, J. E.; Kirby, K.; Thomason, W. E.; Rucker, E. G.; Behl, H. D.; Pitman, R. M.; Dunaway, D. W.; et al.
Abstract : 'LCS Compass' (Reg. No. CV‐1149, PI 675458), a hard red winter (HRW) wheat ( Triticum aestivum L.), was developed and tested as VA10HRW‐13 and co‐released by the Virginia Agricultural Experiment Station and Limagrain Cereal Seeds, LLC, in 2015. LCS Compass was derived from the cross 'Vision 20' /'Stanof' using a modified bulk breeding method. LCS Compass is a widely adapted, high‐yielding, awned, semidwarf ( Rht1 ) HRW wheat with early to medium maturity and resistance or moderate resistance to diseases prevalent in the mid‐Atlantic and Great Plains regions of the United States. In the 2013 Uniform Bread Wheat Trial conducted over 18 locations in eastern states, LCS Compass produced an average grain yield of 4609 kg ha −1 that was similar to 'Vision 30' (4697 kg ha −1 ). In the northern Great Plains, the average grain yield of LCS Compass (4015 kg ha −1 ) over 44 locations in 2013 was similar to 'Jerry' (4013 kg ha −1 ). In the South Dakota crop zone 3 variety test, LCS Compass had a 3‐yr (2015–2017) yield average of 5575 kg ha −1 and was one of highest‐yielding cultivars among the 19 cultivars tested over the 3‐yr period. LCS Compass has good end‐use quality in both the eastern and Great Plains regions of the United States.